Synthesis of naringenin schiff base loaded CMC/PVA scaffold as biodegradable wound care materials - Udaya Rajesh R; Sachin K S; Anagha Bijili Gopakumar; Jijo Thomas Koshy; D Sangeetha (Materials Research Express)
The complex formula of wound care therapy includes effective treatment tactics, infection prevention, wound preconditioning, and germ therapy. By creating ideal circumstances for wound healing, wound dressings are a major factor in lowering the rate at which infections worsen. The persistence of chronic wounds as a significant healthcare challenge necessitates the creation of innovative wound-dressing techniques. This work describes a novel method for creating ternary biodegradable polymers from polyvinyl alcohol (PVA) and carboxymethylcellulose (CMC). With the addition of naringenin Schiff base, the aqueous mixture of CMC and PVA creates an ideal wound dressing material. The naringenin-derived Schiff base demonstrates strong antibacterial and antioxidant activities. The goal of this work is to create, polymer based on polyvinyl alcohol (PVA) and carboxymethylcellulose (CMC) loaded with Naringenin Schiff base for efficient wound care therapy. The ^1 H, ^13 C NMR, FT-IR, and mass spectrometry were used to characterize the Schiff base. The Schiff Base loaded CMC/PVA film was characterized by FT-IR, AFM. Studies such as biodegradability, antimicrobial studies, water absorption capabilities, water vapour transmission rate and dressing pH of the films were also conducted. The promise of biopolymers as better wound dressing material will be highlighted in this work, allowing more efficient wound care.